Multiscale analysis and reduction measures of urban carbon dioxide budget based on building energy consumption - Lin, Tzu-Ping; Hämmerle, Martin; Höfle, Bernhard; Bechtold, Sebastian (Energy and buildings, 2017)
As urban areas continue to develop and expand, carbon dioxide (CO2) emissions from their energy use are growing exponentially. This has made carbon reduction a global concern. Previous studies have provided a limited understanding of carbon budgets because they have used top-down data on a single spatial or temporal scale. In this study, urban spatial and statistical data for metropolitan Tainan in southwestern Taiwan are used to explore inside and outside of the CO2 system of the city and estimate the amount of CO2 emissions from road traffic, the use of electricity and gas in buildings, and the amount of CO2 absorbed by green spaces and water bodies within the system. Innovative annual and monthly carbon budget maps composed of 200×200-m grids are developed for the city through a geographic information system (GIS). An analysis of the highly detailed maps yields the following findings: First, CO2 emissions are concentrated in over-urbanized areas, where the population density is higher than 5000 people/km2. Buildings account for the majority of carbon dioxide emissions (54%) and produced 11% more carbon dioxide in summer than in winter (owing to air-conditioning usage). Second, road traffic is the main source of CO2 emissions for under-urbanized areas (87%), and emissions from this source exhibit insignificant seasonal variation. On the basis of these findings, the carbon budgets of four different over-urbanized areas are formulated and presented on 50×50-m grids. The results suggest that green spaces in these areas absorb limited amounts of carbon dioxide. Therefore, this study assesses the annual and monthly carbon-reduction potential of rooftops equipped with solar panels occupying 30% of their area. The annual carbon-reduction potential for the four areas was 4.5-31.1kgCO2m−2yr−1, and the solar energy replacement rate is higher in winter than in summer. In summary, this study presents carbon budgets in high-resolution grids, quantifies the carbon-reduction potential of rooftops with solar panels, and proposes a reduction strategy for reducing CO2 emissions from urban activities to improve the sustainability of urban areas and their environs and inform urban planning and climate change adaptation.